Capacity Building for Ubi Cilembu Roasted Sweet Potato Small and Medium Enterprises (SMEs) Community at Warung Salapan, Bandung, Through Accounting Information System 'SI APIK' and 'Green Accounting' to Support Sustainable Business - Yulianti, Maria Lusiana; Marditama, Theresia; Harnani, Nining; Nurlaila, Astri; Ariyanti, Widy Dwi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Cilembu Sweet Potato Roastery at Warung Salapan Bandung. Small and medium-sized enterprises (SMEs) operating in the culinary sector often encounter challenges in financial management due to the continued use of manual methods for financial record-keeping. Furthermore, environmental considerations are of paramount importance in this business, given that Cilembu Sweet Potato is the primary ingredient in the culinary products produced, and effective waste management is crucial for sustaining this business. The objective of this Community Service Activity (PKM) is to enhance financial management capabilities through the use of an Accounting Information System. Additionally, providing insights into green accounting can contribute to raising environmental awareness and responsibility among SME stakeholders, thus aiding in the reduction of the environmental impact resulting from business activities while promoting sustainable SMEs. This Community Service Activity offers various methods and approaches to address these issues. These include training sessions, which equip SME stakeholders with knowledge of green accounting and enhance their proficiency in the 'SI APIK' Accounting Information System. The outcomes of this activity reflect its positive contribution to supporting sustainable SME growth and promoting environmental awareness in Warung Salapan Bandung. It also empowers SME owners to manage their businesses more effectively. Additionally, it leads to increased empowerment of partners, higher revenues for partners engaged in the economic sector, and improved understanding and skills within the community.